Solubility of swietenia macrophylla seeds oil in supercritical carbon dioxide extraction - Hilmi, Mohammad Lokman (2020)
Swietenia macrophylla (S.macrophylla) is one of the members of the family Meliaceae. S.macrophylla is commonly known as Swietenia mahagoni in Indonesia and locally known as Tunjuk Langit in Malaysia. It is very popular for various treatments and it contains many useful health properties such as antibacterial, antioxidant, anti-inflammatory and antidiabetic. The main purpose of this research was to investigate the effect of temperature and pressure on the oil yield and solubility of S.macrophylla seeds oil using supercritical carbon dioxide (SC-CO2). Understanding the behavior of the SC-CO2 separation process is fundamental in designing this process. Another objective was to determine the best suited solubility model for S.macrophylla seeds oil using five semi-empirical solvent density-based models. The solubility of S. macrophylla seeds oil in SC-CO2 was determined by using the dynamic method at 20-30 MPa and 40-60 oC at the fixed CO2 flow rate of 2 mL/min. The results showed that an increase in temperature and pressure would increase the oil yield. The highest extract and solubility of S.macrophylla oil was obtained at the highest extraction condition of 60 oC and 30 MPa with 803 mg oil/g sample and 4.77 mg/g CO2 respectively. In this study, five semi-empirical models were tested to fit the experimental data. Results showed that Sparks model was the best-fitted model for S. macrophylla seeds oil solubility data with an average absolute relative deviation of 7.76% and a high coefficient of determination, R2, of 0.992. It can be concluded that the result of this study can be used as reference in widening the scope of research in the area of pressure and temperature with a better improvement of predictive ability.